Charter and Ordinances of the City of Portland and Table of Grades: Together with the Rules of Order, Reports of officers, etc., at 207, Concerning Offenses and Disorderly Conduct, § 2 (1879) - (:unkn) unknown (General Publisher, 1879)
That any person or persons who shall fire any pistol, gun or rifle, or any other species of fire-arms, within the corporate limits of the city, shall, on conviction thereof before the Police Court, be fined not less than five dollars nor more than fifty dollars: Provided, That all circumstances of necessity may be plead as a defense to the offense described in this section; and, provided further, that the Chief of Police may permit upon the national holidays and other days of public celebration any appropriate display of firearms named in this section.
--
Keywords: DISCHARGE